Transformasi Kalender Islam di Turki dari Rukyat ke Hisab - Rofiuddin, Ahmad Adib (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2022)
Turkey has a long history in the study of the Islamic Calendar. Since the arrival of Islam in Turkey, the Islamic Calendar has been the main reference in the administration of the kingdom for hundreds of years. Furthermore, the kingdom also paid special attention to developing the Istanbul Observatory, which was considered the most sophisticated observatory at that time, to support the implementation of the early determination of the Hijri month using the observation (rukyat) method. For hundreds of years running, the use of the Hijri calendar then began to be shifted by the Gregorian Calendar System along with the collapse of the Ottoman Empire. In addition to changing the calendar system, Mustafa Kemal Attaturk also changed the method of determining the beginning of the month from observation (rukyat) to calculation (hisab). Although it has undergone many changes since the birth of the Republic of Turkey, the Turkish government's attention to the Islamic Calendar still continuing. After successfully holding the International Hijri Calendar Unification conference in 1978, in 2016 Turkey also held the same event and introduced the 2016 Turkish criteria. Then, this criterion becomes a reference for several countries in determining the beginning of the Hijri month. Despite getting a lot of criticism regarding the 2016 Turkey Criteria, we need to give appreciation to Turkey for its active role in the development of the Global Islamic calendar discourse.